Spring‐infusors: How a simple and small solution can create king‐sized complexity - Pamela Laird; Charlotte Burr; Fenella J. Gill; André Schultz (Wiley, 2023)
Abstract Aim The aims of the study were to investigate family and hospital staff views about the use of spring‐infusor devices for administration of intravenous antibiotic medications, to examine if the device is acceptable and feasible and to map a process for implementation. Design A qualitative study with a pragmatist approach, within a larger, mixed methods knowledge translation study. Methods Data were collected by semi‐structured interviews with patients who have cystic fibrosis and their parents and focus groups and interviews with hospital staff. Interviews were concluded when no new themes were identified. Thematic analysis and process mapping was undertaken. Results Six parents, nine children and 30 staff were interviewed. Families preferred spring‐infusors. Staff knowledge, experience and attitudes toward spring‐infusor use was varied. All staff acknowledged that their role is to support patient‐centred care. Spring‐infusors are preferred by families and clinicians above other IV administration devices but misconceptions about spring‐infusor use and numerous procedural challenges reduced their use.